Arabic and Islamic influences in modern Malaysian literature - bin Samh, Rosney; Noor, Badr Al-Munir bin Muhammad; Ahmed, Wan Azura Bint Wan; Ishaq, Aisha bint (Journal of Educational and Psychological Sciences, 2017)
This study aimed to reveal the influences of Arabic and Islamic in the personality of Malaysian writers and their literary creations influenced by Arabic literature. The study was based on the comparative approach of the French school in comparative literature on the existence of the conditions of influence and influence among the studied literature. The study deals with the Arab and Islamic influences in the personality of Sheikh Mohamed Zine El Abidine Al Aiderous, who performed the poetry of the Prophetic Poetry, and Sheikh El Sayed Al-Hadi, who created the novel from the impact of Zeinab's novel and Alawi Al-Hadi. Arabic is a channel of communication between Arab and Malaysian writers. Through this language influenced Malaysian literature with some Arab and Islamic influences, where the Malaysian writers learned the Arabic language and read the art of Arabic literature, and then created in a new dress. One of the most prominent findings was that these three writers were influenced by Arabic literature. And the impact of the impact of the emergence of the poetry of the Malaysian prophetic influences of the impact of cold and Mahazip, and the emergence of the first Malaysian novel of the impact of the impact of the novel Zaynab, and the birth of the play Tariq ibn Ziad impact of the impact of the story of Fatah al-Andalus. Perhaps the study opens the comparative areas between the literature to readers.
Keywords: influences; literature; Arabic; Islamic; Malaysian; novel; praises; theatrical